DIGITAL TECHNOLOGY IN THE HOME - PREPARING THE FUTURE USERS OF SMART HOME - SERAFÍN, Čestmír (Trends in education, 2013)
Integration of modern (mainly digital) technologies within the content of education and their integration into the educational process happens most often in the form of didactic resources, but may not always be the case.The average person on a daily encounters with technology that utilizes for work or play, it's a normal part of his life in the future will be no different. Modern household, it is today by modern digital technology base and the young generation to be with these technologies meet and enjoy it. Therefore, the question of their integration into teaching at primary school and it is very important this issue is addressed in this article.
Keywords: Technology; Digital technology; Intelligent House; Man and the world of work